Diglosia en la comunidad indígena Ilumán, cantón Otavalo, provincia Imbabura - Reinoso Lema, Brenda Abigail (2022)
This research was to establish the relationship between Intercultural Bilingual Education and the diglossia between Kichwa and Spanish in the indigenous community of Ilumán, located in the province of Chimborazo. The methodology applied was a qualitative-quantitative approach through which information about the exposed problem was gathered. The type of research was descriptive, which allowed us to describe the causes of the existence of diglossia in Ilumán. The techniques and instruments used for data collection were surveys and interviews through which information was collected to support the observed phenomenon. It was possible to identify the causes for diglossia within the Ilumán indigenous community through the analysis of surveys and interviews. Concluding that young people use Spanish more than Kichwa, while older adults use their native language more, considering Spanish as a second language; it also became evident that the deterioration of Kichwa is due to the lack of practice and teaching of the language. Thus, it was found that the most vulnerable generation in the worsening of Kichwa is the young people since they prefer to speak Spanish for convenience or acceptance.